2019
DOI: 10.17718/tojde.522719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping Study 2012-2017: Quality and Effectiveness Measurement in MOOC

Abstract: Massive Open Online Courses (MOOCs) concentrate an important number of students and are set up as an alternative for acquiring knowledge and continuing education. The objective of this article is to analyze how the quality and effectiveness of the MOOCs were measured in empirical studies between 2012 and 2017. For which a systematic mapping study of articles was performed by using databases of Scopus and Web of Science. These articles were analyzed according to the: (1) context of the publication, (2) type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
5
0
4
Order By: Relevance
“…This is a type of remote learning that enables students to learn outside the physical classroom. As a result, (Quiliano Terreros et al, 2009). This platform has demonstrated that it supports lifelong learning, in acquiring key knowledge and skills and the much-needed life-skill interactions with peers and live-project exposure (Sonwalkar & Maheshkar, 2015).…”
Section: Learning With Moocsmentioning
confidence: 99%
“…This is a type of remote learning that enables students to learn outside the physical classroom. As a result, (Quiliano Terreros et al, 2009). This platform has demonstrated that it supports lifelong learning, in acquiring key knowledge and skills and the much-needed life-skill interactions with peers and live-project exposure (Sonwalkar & Maheshkar, 2015).…”
Section: Learning With Moocsmentioning
confidence: 99%
“…1 The Binational Laboratory for the intelligent management of Energy Sustainability and Technological Training. Webpage: https ://energ ialab .tec.mx/ of the Open Educational Movement, such as gratuity and accessibility [11], and they are characterized by being open, participatory and distributed [12][13][14]. On the other hand, the sustainable development of a country depends on how reliable and stable the supply of energy is and whether it is reasonable in cost and in harmony with its environmental and social requirements [15].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Os critérios pedagógicos incluem a metodologia, objetivos de aprendizagem e flexibilidade. O curso deve ser preparado tendo em conta a aplicação de uma qualidade metodológica aceitável, que inclui o design, avaliação e conteúdo do curso (QUILIANO-T.; RAMIREZ-H.;BARNIOL, 2019). É recomendada a aplicação do conectivismo, proporcionando a interação entre seus membros para troca de informações e enriquecimento mútuo.…”
Section: Indicadores De Qualidadeunclassified
“…Geralmente, a satisfação está diretamente correlacionada com o desempenho dos participantes (DUART et al, 2017), por isso é importante manter os participantes comprometidos e os incentivar a explorar novos conceitos durante o curso. Os instrutores também devem lidar com as emoções que os alunos sentem durante ou ao final do curso (QUILIANO-T.; RAMIREZ-H.;BARNIOL, 2019). Um bom indicador do grau da motivação é a taxa de evasão do curso (QUILIANO-T.; RAMIREZ-H.;BARNIOL, 2019).…”
Section: Indicadores De Qualidadeunclassified
See 1 more Smart Citation